Ganesha sculpture in the Devakoshtha (niche) - Temples of India Project Team (Jio Institute, 2024)
Ganesha sculpture in the devakoshtha (niche) on the bhadra (principal or central projection) of the south-facing wall of Suswani Mata Temple. Framed in a niche composed of two pilaster motifs surmounted by a pediment of gavasksha (dormer window) designs, the main Ganesha image is supported by another small Ganesha in a small frame right above its head. It is a seated, eight-handed image of Ganesha. Some of the visible attributes of the image are pasha (noose), ankush (bullhook), sarpa (serpent), bijapuraka (citron, symbolized as ‘seed of universe’).